A música de Eduardo Guimarães Álvares para percussão: Estudo I, Estudo II (A Falsa Rhumba), Pocema, Pratilheiros Catapimbásticos e Taleas - Rubens José de Oliveira Júnior (2014)
This dissertation studies the Eduardo Guimarães Álvaress pieces written exclusively for percussion instruments (Estudo I, Estudo II - A Falsa Rhumba, Pocema, Pratilheiros Catapimbásticos, Taleas and Rhythmas II). Alvares had an extreme importance to brazilian contemporary music. Besides composing, working with players and bringing innovations in his writing for percussion, he also worked as a director at relevant festivals and cultural institutions. The composition's process of a musical piece goes beyond the decodification of the printed symbols on a score. Some decisions must be made to achieve a result that satisfies the performer, the composer and the audience. The goal of this research is to guide these decisions based on the composers aesthetics, acoustic features of the instruments, technical complications of the instruments, besides the scores symbols that includes harmonic, melodic and rhythmic structure, texture and voicing. As well historical, social and artistic (musical and non-musical) context of Eduardo Álvaress pieces. In order to achieve the most reliable result, it was collected all possible material about the composer: scores, newspaper, magazines, blogs, concert programs, CD notes, interviews with musicians that worked directly with him and conversations with the composer himself. Eduardo Guimarães Alvaress art is a universe and this research shows some of its faces.